The REFLECTS Method: A Systematic and Comprehensive Way to Resolve the Basic Conflict in Positive Psychotherapy - Ali Eryilmaz (The Global Psychotherapist)
In Positive Psychotherapy approach, conflict resolution has a positive effect on reducing the symptoms of psychopathological problems and at the same time increasing the functionality of individuals. According to positive psychotherapy, one of the important conflicts is the basic conflict. The study aims to develop the eight-stage REFLECTS method for resolving basic conflicts. Resolving the basic conflict is at the center of the psychopathological patterns of the clients. The resolution of this conflict makes significant contributions to the enhancement of client functionality. Resolving the basic conflict with more systematic and functional models can contribute to this process. With this developed method, the psychotherapist and the client work together to resolve the client's basic conflicts. In this way, clients learn to satisfy their unfulfilled needs healthily. Concurrently, this method is compatible with the five stages of positive psychotherapy. In the future, the effectiveness of the model investigated by empirical research can be revealed.